Economics in West African Irrigated-Rice Production - Touré, A.A.; Groenewald, J.; Seck, P.A.; Diagne, A.; Grove, B. (2012)
The main objective of this investigation is to contribute to the ongoing debate on the effects of the West African Economic and Monetary Union (WAEMU), common external tariff (CET) measures on the competitiveness of the irrigated-rice production system in Niger. The policy analysis matrix (PAM) approach was used to evaluate the various policy effects, based on farm-level, postharvest and rice-marketing data, as well as the financial and economic parity prices of different brands of imported-rice. Results from the PAM base-scenario model showed that under the evaluated CET policy irrigated rice production, activities were competitive and private operators had positive financial gains, meaning that private profitability was positive. Moreover, the irrigated-rice production enterprise revealed positive economic profitability for both retailers and wholesalers. Thus, it generated a net positive income for the national economy per unit of land devoted to this activity. One can argue that the irrigated rice system under the CET was generally competitive (positive private profitability) and had a potential for growth (positive economic profitability). Despite its competitiveness and efficiency, the irrigated rice production system still performs below potential because it lacks additional incentives. Some sensitivity analyses were performed with single-factor and simultaneous changes of several factors, which confirmed the necessity of providing further incentives to the system. The research results suggest that greater incentives should be given in terms of improving marketing channels, especially for retail rice marketing in which a great number of women rice traders are active.